Errors and intelligence in computer-assisted language learning parsers and pedagogues - Heift, Trude; Schulze, Mathias 1962- (Routledge studies in computer assisted language learning, 2007)
Provides an overview of theoretical issues, developments and trends in ICALL. Assuming a basic familiarity with Second Language Acquisition (SLA) theory and teaching, CALL and linguistics, this book is useful for upper undergraduate and graduate students who study CALL, SLA, language pedagogy, applied linguistics and computational linguistics